(untitled) (Journal of Comparative & International Higher Education, 2023)
The Fulbright Program is the United States’ flagship educational exchange program. Since 1946, the program has been heralded as a program that promotes mutual understanding across cultures. However, the Fulbright Program’s role as a U.S. Department of State initiative warrants further examination of how this educational exchange program functions as a foreign policy effort on behalf of the United States. This mixed methods study uses data presented in five years of data available in the Fulbright Foreign Scholarship Board’s Annual Reports of the program. The study finds seven themes present in the written content of the annual report: Human rights, peace and security; access, diversity, and opportunity; collaboration and partnership; mutual financial investment; excellence as a result of Fulbright; program impact; and solving global problems.